(untitled) - Victoria Kimbrough (New York, 1998)
The book features core vocabulary, acarefully structured grammar syllabus, cross-cultural topics, key learning strategiesintegrated into each unit and consolidated in the Strategy Session review units
Keywords: english language - spoken english - problems, exercises, etc,english language - textbooks for foreign speakers,listening - problems, exercises, etc